The role of adjuvants in regional anesthesia: the postoperative analgesic effectiveness of dexamethasone vs. tramadol given as adjuvants to bupivacaine for ultrasound-guided supraclavicular block for upper extremity surgery—a prospective cohort study - Tadesse, Haregewoin; Sintayhu, Ashagrie; Dendir, Getahun; Tila, Mebratu; Habtu, Elias; Alemu, Afewerk; Alemayehu, Mihiretu (Frontiers in Anesthesiology, 2024)
Background Brachial plexus block is used as a surgical anesthesia and analgesia for postoperative pain. Recently, the use of local anesthetics for regional nerve block has been enhanced by mixing them with a different class of drugs as adjuvants. These adjuvants of local anesthetics improved the quality and duration of nerve block and reduced the dose-dependent side effects of local anesthetics. However, the effectiveness of these adjuvants varies depending on the nature of the nerve block and the type of local anesthetics used. Therefore, we aimed to compare the postoperative analgesic effectiveness of dexamethasone vs. tramadol when used as adjuvants to bupivacaine for ultrasound-guided supraclavicular block in upper extremity surgery. Methods Utilizing a prospective cohort study design, 126 consecutive patients who were undergoing upper extremity surgery with ultrasound-guided supraclavicular block were included. Patients were divided into three groups based on the preference of the responsible anesthetist to use adjuvants with bupivacaine for the block. The dexamethasone group (n = 42) were given 30 ml of 0.25% bupivacaine with 8 mg dexamethasone, the tramadol group (n = 42) were given 30 ml of 0.25% bupivacaine with 100 mg tramadol, and the non-adjuvant group (n = 42) were given 30 ml of 0.25% bupivacaine alone. The primary outcomes evaluated were postoperative pain severity using the numerical pain rating scale (NRS), the duration of analgesia, and the total postoperative analgesic consumption. Secondary outcomes included the incidence of postoperative complications. Result A total of 126 patients were recruited and analyzed. There was no statistical difference in the demographic data among the groups. The postoperative NRS score was significantly reduced in the dexamethasone and tramadol group compared with the non-adjuvant group (p < 0.001). The NRS score in the dexamethasone group at 18 and 24 h was statistically much lower than in the tramadol and non-adjuvant group. The postoperative duration of analgesia was significantly prolonged in the dexamethasone (1,069 ± 316.99 min) group compared with the tramadol (617.02 ± 214.05 min) and non-adjuvant (434.17 ± 111.23 min) groups (p < 0.001). Patients in the non-adjuvant group had a significantly higher total analgesic consumption over 24 h. The dexamethasone group experienced significantly fewer incidences of nausea, with no differences in other complications among the groups. Conclusion The addition of dexamethasone as an adjuvant to bupivacaine for ultrasound-guided supraclavicular block improves postoperative analgesia. We recommend the integration of dexamethasone as an adjuvant to local anesthetics during nerve blocks to enhance postoperative pain management after surgery.